Pattern recognition and machine intelligence : 6th International Conference, PReMI 2015, Warsaw, Poland, June 30-July 3, 2015 : proceedings /: 6th International Conference, PReMI 2015, Warsaw, Poland, June 30-July 3, 2015 : proceedings. (2020) - Unknown
No abstract available